Finland : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Finland's strong economic record has stalled. The economy has been in recession for three of the last five years, and unemployment is now more than 8 percent, with more people without work for longer. The shortfall in growth, coming at a time when peer economies saw GDP improve and unemployment fall, points to deeper structural problems. Exports suffered from the continued decline of the information and communications technology industry and falling demand for paper and pulp. The outlook is for a slow and fragile recovery, and weaker external demand could easily derail the upswing.